The Influence of E-Learning on Innovative Work Behavior in Companies: A Theoretical Review - Kartini, Tri Mulyani; Sariwulan, Tuty; Dara, Despinur; Susita, Dewi (IJHCM (International Journal of Human Capital Management), 2024)
This study aims to examine the influence of e-learning on Innovative Work Behavior (IWB) within corporate environments through a theoretical literature review. The research employed a qualitative approach using a literature review method by analyzing 20 peer-reviewed journal articles sourced from databases such as Publish or Perish and Mendeley. Of these, 11 studies utilized quantitative methods while the rest applied qualitative approaches. The articles were selected using non-probability sampling techniques, including random and snowball sampling, focusing on keywords such as e-learning, digital learning, and training. VOS viewer was used for bibliometric analysis and visualization of research trends related to e-learning. The findings reveal that e-learning has developed significantly and is closely associated with key factors such as digital learning, learning motivation, learning effectiveness, and employee performance. E-learning platforms have shown to not only improve knowledge transfer and training efficiency but also encourage innovative behaviors among employees by enhancing flexibility, collaboration, and engagement. Visualization analysis showed a growing trend in research related to e-learning and innovation, with several research areas still underexplored, particularly regarding how digital learning influences the generation and implementation of new ideas at work. This study concludes that e-learning serves as a strategic tool for developing innovative work behavior, contributing both to organizational performance and to the advancement of knowledge in human resource management and educational technology.